ANALISIS KEMAMPUAN STRUCTURE SENSE DALAM MATERI PEMANGKATAN BENTUK ALJABAR PADA SISWA MTs ASSALAM - Siti Nafiah; Junarti Junarti; Ifa Khoiria Ningrum (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2020)
This article aims to determine the extent to which the ability to structure sense in the form of material binding a^2-b^2=(a-b)(a+b). This type of research is qualitative research. The subjects of this study were students of class VII-B MTs ASSALAM Bangilan, amounting to 25 students. However, only six subjects were analyzed based on the ability indicators of structure sense in terms of the same answer patterns. The research instrument consisted of test questions and interview guidelines. Data analysis techniques used in the model of Miles and Huberman include data reduction, data presentation, and concluding. The study results showed that in question number 1, 40% of students could sense structure, and 60% are less familiar with the sense of structure due to each deployment's completion, not using the form a^2-b^2=(a-b)(a+b). In question number 2, 32% of students can structure sense, and 68% are less familiar with the sense of structure due to a^2-b^2=(a-b)(a+b) sensitivity is still low, and the answer pattern describes each appointment. Whereas in question number 3, only 28% can structure sense, and 72% lack familiarity with structure sense because they cannot manipulate structures properly. In conclusion, the ability to structure sense to form a^2-b^2=(a-b)(a+b) students is still low. Artikel ini bertujuan untuk mengetahui sejauhmana kemampuan structure sense pada materi pemangakatan bentuk a^2-b^2=(a-b)(a+b). Jenis penelitian ini menggunakan penelitian kualitatif. Subyek penelitian ini adalah siswa kelas VII-B MTs ASSALAM Bangilan yang berjumlah 25 siswa, akan tetapi hanya diambil 6 subyek yang dianalisis berdasarkan indikator kemampuan structure sense ditinjau dari pola jawaban yang sama. Instrumen penelitian terdiri dari soal tes dan pedoman wawancara. Teknik analisis data menggunakan model Miles dan Huberman meliputi reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa pada soal no. 1, 40% siswa memiliki kemampuan structure sense dan 60% kurang mengenal structure sense disebabkan dalam penyelsaiannya menjebarkan masing-masing pemangkatan, tidak menggunakan bentuk a^2-b^2=(a-b)(a+b). Pada soal no. 2, 32% siswa memiliki kemampuan structure sense dan 68% kurang mengenal structure sense disebabkan kepekaan struktur pemangkatan a^2-b^2=(a-b)(a+b) masih rendah, dan pola jawabannya menjabarkan masing-masing pemangkatan. Sedangkan pada soal no. 3 hanya 28% yang memiliki kemampuan structure sense dan 72% kurang mengenal structure sensedisebabkan tidak dapat memanipulasi struktur dengan tepat. Kesimpulannya kemampuan structure sense pemangakata bentuk a^2-b^2=(a-b)(a+b) siswa masih rendah.